Endophytic Bacillus vallismortis and Bacillus tequilensis bacteria isolated from medicinal plants enhance phosphorus acquisition and fortify Brassica napus L. vegetative growth and metabolic content - Nagah, Aziza; El-Sheekh, Mostafa M.; Arief, Omnia M.; Alqahtani, Mashael Daghash; Alharbi, Basmah M.; Dawwam, Ghada E. (Frontiers in Plant Science, 2024)
Phosphorus fertilization imposes critical limitations on crop productivity and soil health. The aim of the present work is to explore the potential of two phosphate solubilizing bacteria (PSB) species in phosphorus supplementation of Canola (Brassica napus L.). Out of 38 bacterial isolates obtained from 9 medicinal plants, two bacterial strains (20P and 28P) were proved as the most potent for the in vitro tricalcium phosphate solubilization test. These isolates verified their activity toward different enzymes as nitrogenase and alkaline phosphatase. Also, 20P and 28P gave a high amount of IAA, 34.16 and 35.20 μg/ml respectively, and were positive for siderophores production as they detected moderate affinity for iron chelation. Molecular identification confirmed that strain 20P was Bacillus vallismortis and strain 28P was Bacillus tequilensis. A pot experiment was conducted to study the effect of four different phosphorus concentrations (0, 50, 75, and 100 %P) each alone and/or in combination with B. vallismortis, B. tequilensis, or both bacterial isolates on the vegetative growth and some physiological parameters of canola. The combined treatment of 50 % phosphorus + (B. vallismortis + B. tequilensis) was generally the most effective with respect to shoot height; shoot dry mass, leaf area, photosynthetic pigment fractions, total sugar content, and accumulated NPK content. In contrast, the rhizosphere pH reached the minimum value under the same treatment. These findings highlighted the potential use of PSB (B. vallismortis and B. tequilensis) along with phosphorus fertilization as a safe sustainable tactic.